2018
DOI: 10.1029/2018gc007908
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Gametogenic Calcification and Dissolution on δ18O Measurements of the Planktic Foraminifer Trilobatus sacculifer

Abstract: Oxygen isotope ratios (δ18O) measured from planktic foraminifer shells are commonly used to reconstruct past surface ocean conditions, yet the shells of many planktic foraminifers are an aggregate mixture of multiple carbonate phases with differing δ18O compositions. Here we demonstrate how secondary ion mass spectrometry can be used to measure intrashell δ18O heterogeneity by performing in situ analyses on micrometer‐scale (3–10 μm) domains within individual shells of the extant, mixed layer species Trilobatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…For example, the outermost chamber of T. sacculifer comprises two different calcite structures with ontogenetic calcite on the inner side and gametogenic calcite on the outer side. SEM observation of the outermost chamber wall structure of T. sacculifer revealed gametogenic calcite on the outer side, an ontogenetic calcite layer on an intermediate layer of chamber wall, and an inner calcite layer on the inside of a primary organic sheet (Wycech et al, ). Furthermore, our XMCT scan results are consistent with cross section SEM images of T. sacculifer tests from several core top samples that showed selective dissolution of the ontogenetic calcite layer on an intermediate layer of the outermost chamber wall as suggested in Wycech et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the outermost chamber of T. sacculifer comprises two different calcite structures with ontogenetic calcite on the inner side and gametogenic calcite on the outer side. SEM observation of the outermost chamber wall structure of T. sacculifer revealed gametogenic calcite on the outer side, an ontogenetic calcite layer on an intermediate layer of chamber wall, and an inner calcite layer on the inside of a primary organic sheet (Wycech et al, ). Furthermore, our XMCT scan results are consistent with cross section SEM images of T. sacculifer tests from several core top samples that showed selective dissolution of the ontogenetic calcite layer on an intermediate layer of the outermost chamber wall as suggested in Wycech et al ().…”
Section: Discussionmentioning
confidence: 99%
“…SEM observation of the outermost chamber wall structure of T. sacculifer revealed gametogenic calcite on the outer side, an ontogenetic calcite layer on an intermediate layer of chamber wall, and an inner calcite layer on the inside of a primary organic sheet (Wycech et al, ). Furthermore, our XMCT scan results are consistent with cross section SEM images of T. sacculifer tests from several core top samples that showed selective dissolution of the ontogenetic calcite layer on an intermediate layer of the outermost chamber wall as suggested in Wycech et al (). The fact that our XMCT scans revealed such selective dissolution of an intermediate calcite layer of the outermost chamber wall also in G. ruber tests suggests that test dissolution of these two species is characterized by selective dissolution of early developed calcite formed during the juvenile stage and the ontogenetic calcite layer on an intermediate layer of the outermost chamber wall, and preservation of gametogenic calcite on the outer side and the inner calcite layer on the inner side of the primary organic sheet.…”
Section: Discussionmentioning
confidence: 99%
“…The Mg/Ca-based SSTs were calculated using the T. sacculifer calibration of Dekens et al (2002). This Mg/Ca-temperature calibration includes a dissolution correction based on water depth that is deemed appropriate for SST reconstruction since foraminifer dissolution is prevalent in the equatorial Pacific (e.g., Fehrenbacher & Martin, 2011;Mekik et al, 2007;Rongstad et al, 2017;Rosenthal et al, 2000;Thompson & Saito, 1974;Wycech et al, 2018). Although the degree of dissolution likely varied slightly through the study interval (Pälike et al, 2012), a temporal adjustment to ΔCO 3 2− has a negligible effect on the reconstructed SST trend (see Appendix A).…”
Section: 1029/2019pa003685mentioning
confidence: 99%
“…1, scenarios A and B), the calcite produced in such a way may be indistinguishable isotopically from older chambers. Whilst the size of this bias induced by GAM may have been overestimated in the literature, for instance using cultures, Hamilton et al (2008) showed that approximately 80 % of the shell material is pre-GAM; new evidence suggests that the δ 18 O between pre-GAM and GAM is ∼ 1 ‰ (Wycech et al, 2018). The same work suggests that GAM comprises 32 % to 44 % of T. sacculifer shells.…”
Section: Difference Between F and < F : An Underestimation?mentioning
confidence: 99%